EFEKTIVITAS SANKSI PIDANA TERHADAP PELAKU INSES DALAM MENANGANI KEJAHATAN SEKSUAL DALAM KELUARGA - Abdurrahman, U.; Syaripudin, Dadang; Novianti, Linda (Jurnal Hukum Media Justitia Nusantara, 2022)
This research aims to analyse the sexual crime of incest within the family which is a form of human rights violation and violates ethical, moral norms and contradicts the basic principles of law. This research is a qualitative research with a normative juridical approach. The technique used is library research. This research concludes that: Firstly, incest is illegal in many jurisdictions and is considered an unethical and socially unacceptable act in society. Thus, incest has serious consequences, including potential physical and psychological damage to children born from the relationship and can also lead to the fracturing of family relationships as a whole. Second, the effectiveness of criminal sanctions for incest perpetrators can be influenced by various factors, namely the application of adequate and balanced penalties is important to provide a deterrent effect on the perpetrators of incest. In addition, the consistency of the application of criminal sanctions against the perpetrators of incest and the accuracy in law enforcement for the guilty perpetrators must be punished appropriately, indiscriminately, and without any form of discrimination. Third, the role of the judicial system in dealing with sexual crimes of incest in enforcing the law and processing cases of sexual crimes of incest in accordance with applicable laws. Victims of incestuous sexual crimes should be given appropriate protection, including the provision of safe facilities to report crimes, counselling programmes, and support for those involved.